1986
DOI: 10.1901/jaba.1986.19-93
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Reciprocal Peer Tutoring and Group Contingencies on the Academic Performance of Elementary School Children

Abstract: We evaluated the effects of reciprocal peer tutoring combined with group reinforcement contingencies on the arithmetic performance of 12 underachieving fifth-grade students. Results indicated that the intervention increased the students' arithmetic performance to a level indistinguishable from their classmates during treatment and 12-week follow-up phases. Pre-, post-, and follow-up sociometric data indicated that the students who participated in the treatment groups increased their amount of peer affiliation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
3

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 8 publications
3
36
0
3
Order By: Relevance
“…Another way of integrating positive peer experience with academic content is having more capable children assist their classmates who are in academic difficulty. Pigott, Fantuzzo and Clement (1986) arranged peer tutoring for primary school pupils weak in arithmetic. They found that this procedure resulted in improved arithmetic achievement.…”
Section: Social and Cultural Ecology Of The Schoolmentioning
confidence: 99%
“…Another way of integrating positive peer experience with academic content is having more capable children assist their classmates who are in academic difficulty. Pigott, Fantuzzo and Clement (1986) arranged peer tutoring for primary school pupils weak in arithmetic. They found that this procedure resulted in improved arithmetic achievement.…”
Section: Social and Cultural Ecology Of The Schoolmentioning
confidence: 99%
“…Reciprocal peer tutoring: a highly structured framework RPT was originally and successfully developed by Fantuzzo and his colleagues to enhance scholastic competency and self-control in elementary-level students at high risk of academic failure (e.g., Pigott et al 1986;Wolfe et al 1986). Children were given specific guidelines and materials (i.e., flash cards, worksheets) that allowed them to prompt, monitor, evaluate, reward group attainment, and encourage each other.…”
mentioning
confidence: 99%
“…Les autres différences entre groupe témoin et expérimental que nous n'avons pas contrôlées strictement sont liées au recours à l'informatique et à un accroissement probable des échanges métalinguistiques entre les élèves. En effet, il est commun d'observer des effets de cette coopération sur les améliorations de résultats des élèves, et pas simplement dans le domaine de la lecture (Greenwood et collab., 1984 ;Greenwood et collab., 1987 ;Pigott, Fantuzzo et Clement, 1986). Aussi, on pourrait imputer le gain de compréhension que nous observons dans ces expérimentations au seul effet de la coopération avec des pairs.…”
Section: Discussionunclassified